2020
DOI: 10.1002/smi.2954
|View full text |Cite
|
Sign up to set email alerts
|

Associations between stressful life events, non‐suicidal self‐injury, and depressive symptoms among Chinese rural‐to‐urban children: A three‐wave longitudinal study

Abstract: Migrant children experience more stressful life events than their urban counterparts. Despite the growing evidence that stressful life events are associated with nonsuicidal self-injury (NSSI), few studies have investigated this relationship using longitudinal designs. Besides, potential mediating factors have been rarely examined. This study tested the temporal relationship between stressful life events and NSSI among Chinese rural-to-urban migrant children, with depressive symptoms as the potential mediator,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 61 publications
5
24
0
Order By: Relevance
“…In tests of the mediated path, we found that depressive symptoms partially mediated the relationship between stressful life events and sleep problems. This nding is in line with evidence that depressive symptoms mediate the association between stressors and adaptive problems including non-suicidal selfinjury (Gao et al, 2020) as well as problematic smartphone usage (Xie et al, 2020). The stage model of stress and disease (Cohen et al, 2016) could explain this mediated path.…”
Section: Insert Figure 3 Insert Figure 4 Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In tests of the mediated path, we found that depressive symptoms partially mediated the relationship between stressful life events and sleep problems. This nding is in line with evidence that depressive symptoms mediate the association between stressors and adaptive problems including non-suicidal selfinjury (Gao et al, 2020) as well as problematic smartphone usage (Xie et al, 2020). The stage model of stress and disease (Cohen et al, 2016) could explain this mediated path.…”
Section: Insert Figure 3 Insert Figure 4 Discussionsupporting
confidence: 85%
“…Biological mechanisms are revealed as stress up-regulate individual proin ammatory cytokines, and in turn elicit profound behavioral changes including the initiation of depressive symptoms (Slavich & Irwin, 2014). Consistently, researches have shown that adolescents experiencing more stressful life events are inclined to exhibit more depressive symptoms (Barra et al, 2019;Gao et al, 2020). In addition, longitudinal studies have shown that stressful life events predict later depressive symptomatology, even allowing for earlier symptoms of depression (Evans et al, 2015;Ghobadzadeh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Last, we should notice that the results of attrition analysis showed that drop-out rates were higher among adolescents reporting depressive symptoms and self-harming behaviors. Because of this methodological limitation, and given that some longitudinal studies showed an association between depressive symptoms and self-harm (Gao et al, 2020), our longitudinal findings need to be interpreted with caution, and further studies are needed to replicate our results.…”
Section: Limitationsmentioning
confidence: 84%
“…Stressful life events (such as family conflicts, conflict with teachers, classmate disputes, economic distress, death of relatives, and failure in examination) are important predictors of adolescent NSSI (Gao et al, 2020). Nock's (2010) integrated theoretical model of NSSI proposes that NSSI is an effective means of regulating social situations, which has a function of interpersonal negative reinforcement (e.g., NSSI facilitates stop from family conflicts).…”
Section: Stressful Life Events and Adolescent Nssimentioning
confidence: 99%